PENINGKATAN PRODUKTIVITAS KERJA ALAT MUAT-SARAD SERBAGUNA EXP-2000 HASIL PERBAIKAN - Wesman Endom; Semedi Tohdjaya; Yayan Sugilar (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
The EXP-2000 is a multipurpose equipment designed for use in logging operation. especially for loading and skidding of logs. In the first trial conducted in 2001, the productivity of EXP-2000 turned out to be very low i.e. 0.872 m3hm/hour. The investment cost of EXP-2000 was about Rp 67.5 million so the cost of operation was Rp. 28,736.25 per hour. After improvement in the performance has been improved: skidding productivity was increased to 3.293 m3.hm/hour and production cost of was reduced Rp 8. 725.29 per m3.In loading operation, the performance of EXP-2000 has been improved by increasing productivity from 3.293 m3.hm/hour to 34.705 m3/hour and decreasing the cost from Rp. 5,315 per m3 to Rp. 828.03 per m3. It means that the implementation of a new improved EXP-2000 is promising both technically and economically due to higher productivity compared to that of using animal (buffalo) and conventional skyline system previously developed by the Research and Development Center for Forest Product Technology, Bogor - Indonesia.